Fatal Interstitial Pneumonia as an Advers Reaction in Patient with Rheumatoid Arthritis: A Case Report - Sedat Kaya,; Selim Turhanoğlu,; Ayşe Dicle Turhanoğlu, (Archives of Rheumatology, 2008)
Acute interstitial pneumonia developed three weeks after the administration of leflunomide(LEF) in a 53-year-old woman with rheumatoid arthritis. She developed nausea and diarrhea as well as dyspnea before coming to the hospital and LEF treatment was stopped. She suddenly experienced severe dyspnea and her chest x-ray showed reticular shadows in her lower lung fields which had not been detected before. Partial oxygen pressure of her arterial blood fell all of a sudden, which necessitated an emergency admission to the intensive care unit. After endotracheal intubation, mechanical ventilation support was started due to acute respiratory failure. The patient died of respiratory failure 7 days after the onset of acute interstitial pneumonia (Rheumatism 2008; 23: 103-5)